2011
DOI: 10.1002/gcc.20857
|View full text |Cite
|
Sign up to set email alerts
|

Loss at chromosome arm 16q in retinoblastoma: Confirmation of the association with diffuse vitreous seeding and refinement of the recurrently deleted region

Abstract: In addition to mutations in both alleles of the retinoblastoma gene (RB1) alleles, retinoblastomas frequently show additional alterations including loss of chromosome arm 16q. In a previous study, the presence of 16q alterations was found to be associated with diffuse vitreous seeding of this tumor. This growth pattern is clinically important as it determines therapeutic decisions. The present study was designed to test this association and to narrow down the list of candidate genes in the minimal region of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…This suggests a biparental germinal contribution of both D13 chromosomes to the Rb phenotype. A biparental-specific share of the alleles of chromosome 16 was also observed, which represents information of additional interest in this family since deletion of the long arm of this chromosome (16q) is related to a particular type of Rb [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a biparental germinal contribution of both D13 chromosomes to the Rb phenotype. A biparental-specific share of the alleles of chromosome 16 was also observed, which represents information of additional interest in this family since deletion of the long arm of this chromosome (16q) is related to a particular type of Rb [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retinoblastoma has a natural tendency to infiltrate and disseminate and intravitreal seeding is an important characteristic of this tumor. It has been suggested that tumors with local and diffuse intravitreal seeding were genetically distinct and that loss of chromosome 16q was strongly associated with diffuse seeding (14). As the intraretinal tumor grows, necrosis, inflammatory reaction, and increased intratumoral pressure lead to a breach in the internal limiting and posterior hyaloid membranes and result in liquefaction of the neighboring vitreous and tumor herniation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the 1q gain and 16q loss in tumors are indicative of increased levels of genomic instability and associated with late diagnosis and non-hereditary retinoblastoma [ 27 , 28 , 31 , 33 ]. Recurrent loss of 16q is believed to impair candidate suppressor genes and is implicated in advanced disease [ 34 , 35 , 36 ]. MYCN gain/amplification occurs in approximately 8% of retinoblastoma and is included in the most common focal genomic aberration [ 24 , 37 , 38 ].…”
Section: Molecular and Cellular Basis Of Retinoblastomamentioning
confidence: 99%